RACIAL AND CULTURAL IDENTIFICATION CHALLENGES IN FACIAL RECOGNITION: A CENTRAL ASIAN PERSPECTIVE - Yunusova, Nodira (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
This paper examines the racial and cultural identification challenges of facial recognition technologies from a Central Asian perspective. Despite rapid adoption in security, governance, and digital services, most systems are trained on datasets dominated by Western and East Asian populations, leading to misidentification of Central Asian ethnic groups. Diverse phenotypes, traditional attire, and inconsistent biometric standards further reduce accuracy. Weak legal frameworks and limited public awareness heighten risks of bias, privacy violations, and misuse. The paper emphasizes the need for inclusive datasets, culturally informed system design, and strong regulatory protections to ensure fairness, representation, and ethical implementation in the region.